Rating-Based Investment Practices and Bond Market Segmentation - Chen, Zhihua; Lookman, Aziz A.; Schürhoff, Norman; Seppi, Duane J. (The Review of Asset Pricing Studies, 2014)
This paper documents a new channel for rating-based bond market segmentation, which, in contrast to prior research, is based on nonregulatory investment management practices. A 2005 Lehman Brothers index redefinition provides a quasinatural experiment in which a number of previously high-yield split-rated bonds were mechanically relabeled as investment grade. Although their regulatory standing was unaffected, these bonds had abnormal yield declines of 21 basis points. These valuation changes can be traced to buying by asset-class-sensitive institutional investors for whom these bonds became investable. Reputation, regulation, indexation, and liquidity cannot explain the observed price and trading patterns. (JEL G12, G14)